Preoperative prognostic factors for functional and clinical outcomes after open partial horizontal laryngectomies. Issue 11 (18th August 2021) - Fantini, Marco; Crosetti, Erika; Affaniti, Riccardo; Sprio, Andrea Elio; Bertotto, Ilaria; Succo, Giovanni
Abstract: Background: In minority of cases, the clinical recovery of the neolarynx after open partial horizontal laryngectomies (OPHLs) can be challenging, possibly affecting the final functional outcome. Methods: One hundred and twenty‐three patients who underwent OPHLs were selected. A series of clinical preoperative independent variables were considered. All patients were monitored for the following dependent outcome variables: sequelae; need for percutaneous endoscopic gastrostomy positioning; days before tracheal cannula removal and nasogastric tube removal; and length of hospital stay. Univariate and multivariate logistic regression analyses were performed to identify significant associations between preoperative clinical variables and outcomes variables. Results: Multivariate analysis confirmed age, cT classification, body mass index, and smoking habits as significant prognostic factors for worse functional and clinical recovery outcomes. Conclusions: Knowing what variables are significantly associated with worse clinical and functional outcomes can guide clinicians in defining the best surgical choice not only from an oncological perspective, but also for a better postoperative recovery.